Consistent Prebiotic Effect on Gut Microbiota With Altered FODMAP Intake in Patients with Crohn's Disease: A Randomised, Controlled Cross‐Over Trial of Well‐Defined Diets. Issue 4 (April 2016) - Halmos, Emma P; Christophersen, Claus T; Bird, Anthony R; Shepherd, Susan J; Muir, Jane G; Gibson, Peter R
Abstract : OBJECTIVES: : Altering FODMAP (fermentable oligosaccharides, disaccharides, monosaccharides and polyols) intake has substantial effects on gut microbiota. This study aimed to investigate effects of altering FODMAP intake on markers of colonic health in patients with Crohn's disease. METHODS: : After evaluation of their habitual diet, 9 patients with clinically quiescent Crohn's disease were randomised to 21 days of provided low or typical ("Australian") FODMAP diets with ≥21‐day washout in between. Five‐day fecal samples were collected at the end of each diet and analyzed for calprotectin, pH, short‐chain fatty acids (SCFA) and bacterial abundance. Gastrointestinal symptoms were recorded daily. RESULTS: : Eight participants collected feces and were adherent to the diets. FODMAP intake differed across the three dietary periods with low<habitual<Australian diet. SCFA, pH and total bacterial abundance remained unaltered, but relative abundance was higher for butyrate‐producing Clostridium cluster XIVa ( P =0.008) and mucus‐associated Akkermansia muciniphila ( P =0.016), and lower for Ruminococcus torques ( P =0.034) during the Australian compared with low FODMAP diet. Results during habitual diet were similar to the low FODMAP intervention, but significantly different to the Australian diet. The diets had no effects on calprotectin, but symptoms doubled in severity with the Australian diet ( n =9; P <0.001). CONCLUSIONS: : In clinically quiescent Crohn's disease, altering dietary FODMAP intake is associated with marked changes in fecal microbiota, most consistent with a prebiotic effect of increasing FODMAPs as shown in an irritable bowel/healthy cohort. This strategy might be favorable for gut health in Crohn's disease, but at the cost of inducing symptoms.